Fathers' experiences with their preterm babies admitted to neonatal intensive care unit: A multi‐method study. (14th February 2018) - Stefana, Alberto; Padovani, Ezio Maria; Biban, Paolo; Lavelli, Manuela
Abstract: Aim: The aim of this study was to investigate fathers' emotional experiences of their infant's preterm birth and subsequent stay in neonatal intensive care unit. Background: When a baby is born preterm, there is also the premature interruption of the process of preparation for fatherhood. As a result, the impact on fathers of the preterm birth can bring negative consequences for the development of father–infant relationship. Design: A multi‐method approach was used which included ethnographic observation, semi‐structured interviews with fathers, a self‐report questionnaire and clinical information between September 2015–March 2017. Method: Data were analysed using a mixed‐method: a thematic analysis of data from the interviews and quantitative analyses to detect possible clusters of fathers' emotional experiences and associations between clusters and fathers' and/or infants' characteristics. Results: Two clusters were identified. The "fathers‐of‐preterm‐infants" touched their baby as soon as they were given the opportunity and without fear that they would harm their infant. They were struck by their baby's physical appearance. In contrast, the "preterm fathers" preferred not to touch their baby when first given the chance, for fear of breaking/damaging/infecting her/him. They were struck both by the baby's physical appearance and by the technology/equipment around her/him and were afraid that their infant would die. All the "fathers‐of‐preterm‐infants", but only just over half of the "preterm fathers", were actively engaged in their infant's care. Clusters were associated with the infant's gestational age. Conclusion: Fathers of preterm infants should receive personalized support specifically addressed to them and based on the infant's gestational age.